The Role of Micro, Small and Medium Enterprises (MSMEs) In Promoting SDGs in Blitar - Shanti Ike Wardani; Ika Rachmawati (Enrichment : Journal of Management, 2022)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the development of the national economy and employment with a proportion of 99.99% of all business actors in Indonesia. In today's digital era, MSMEs are required to be able to take advantage of economic opportunities and increase competitiveness. The writing of this article was conducted to determine the level of development of MSMEs, the development of the SDGs program, and the influence of the role of MSMEs in encouraging the SDGs in Blitar City. The approach used is the concept of Sustainable Development Goals (SDGs) specifically for the City of Blitar. The sample used was 80 respondents randomly / random sampling from the population of MSME actors in the city of Blitar without any age, education, occupation and other specifications due to the limitations of the researcher. The results of the t-test analysis showed that the role of MSMEs in encouraging SDGs in Blitar City obtained results which can be stated that the role of MSMEs variable has a t value of 0.025 < 1.6643, which means partially the role of MSMEs has no significant effect in encouraging SDGs in Blitar City.